Volume Home Building: The Provision of Sustainability Information for New Homebuyers - Georgia Warren-Myers; Erryn McRae (Construction Economics and Building, 2017)
The new residential housing sector is producing approximately 200,000 homes a year that could benefit from methods to increase sustainability and energy efficiency. Currently, there is limited implementation of sustainability measures beyond mandatory minimum requirements in Australia. New homebuyers are often the scapegoats for the poor sustainability adoption due to their perceived lack of interest and willingness to pay. However, their knowledge and engagement in sustainability is likely to be strongly guided by information provided by the volume builders. This paper investigates the sustainability information that homebuyers are provided by builders, as communicated through their websites. Web searching as an important means of information gathering in the preliminary stages of the process for new homebuyers. This paper reports on the analysis of Australia’s Home Industry Association’s top 100 volume builders’ websites and their provision of sustainability information. The results suggest the lack of sustainability-related information provided by builders is contributing to disengagement by consumers in the sustainability features available in new homes.